Novel features of the rat model of inflammatory bowel disease based on 2,4,6-trinitrobenzenesulfonic acidinduced acute colitis - Szalai, Zita; Kupai, Krisztina; Veszelka, Médea; Pósa, Anikó; Török, Szilvia; Magyariné Berkó, Anikó; Baráth, Zoltán; László, A. Ferenc; Varga, Csaba (Acta Biologica Szegediensis, 2014)
The 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced acute inflammatory bowel disease (IBD) model in the rat is discussed, focusing on the details of the TNBS instillation and highlighting the advantages and limitations of this model. For determination of the time-dependent action of 50% ethanol and different doses of TNBS, male Wistar rats were treated with 50% ethanol or 10 mg or 30 mg of TNBS dissolved in 50% ethanol. The TNBS-induced inflammation peaked 48-72 h after installation and the colitis caused by 30 mg of TNBS was more severe than that caused by 10 mg of TNBS. To test the effectiveness of sulfasalazine (SASP), male rats were treated with 10 mg of TNBS or with 10 mg of TNBS and SASP, and 72 h later the extent of mucosal damage was determined. Orally administered 50 mg/kg/day SASP proved to reduce the TNBS-induced colonic inflammation in rats significantly. The TNBS-induced colitis model facilitates a better understanding of the immunopathological mechanisms of IBD. Optimization of the dose of TNBS and oral SASP as positive control in TNBS-induced colitis in rats furnishes an appropriate test system for new anti-IBD drugs.